2017
DOI: 10.2139/ssrn.3091570
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Energy Efficiency in German Manufacturing: A Firm-Level Stochastic Frontier Analysis

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Many scholars [13][14][15][16] consider R&D efficiency and innovation performance as part of technological innovation efficiency. The logarithm value of the sum of invention and patents is generally used to represent innovation performance, but this method has not been standardized [17,18]. It is important to standardize the important technology and service protection system of Chinese internet companies [9], rather than relying on simple summation.…”
Section: Technological Innovation Efficiency Of Internet Companiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars [13][14][15][16] consider R&D efficiency and innovation performance as part of technological innovation efficiency. The logarithm value of the sum of invention and patents is generally used to represent innovation performance, but this method has not been standardized [17,18]. It is important to standardize the important technology and service protection system of Chinese internet companies [9], rather than relying on simple summation.…”
Section: Technological Innovation Efficiency Of Internet Companiesmentioning
confidence: 99%
“…This approach can be used to assess the fitting quality of the model and provide various statistical test values. To improve the accuracy of efficiency estimation, the SFA method is widely used to measure random errors and invalid rate terms [17,18]. SFA fully considers the interference of random factors, resulting in greatly improved measurement accuracy.…”
Section: Technological Innovation Efficiency Of Listed Internet Compamentioning
confidence: 99%
“…For example, accounting for endogeneity through the use of instrumental variables, Roy and Yasar (2015) find that exporting leads to lower fuel consumption relative to electricity use for Indonesian firms. Using the same dataset on German manufacturers as this paper, Lutz et al (2017) show that exporting firms are more energy efficient than their counterparts.…”
Section: Heterogeneous Treatment Effectsmentioning
confidence: 96%
“…Moreover, exporting may improve management practices (Bloom and Van Reenen, 2010), which in turn may have positive spillovers on energy efficiency Martin et al, 2012;Boyd and Curtis, 2014). Exporting German manufacturers in particular have been found to be more energy efficient than their non-exporting counterparts (Lutz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they showed that energy policy, funding schemes, and administrative structures play an import role in the energy transition of modern communities. Lutz et al [32] demonstrated that exporting, innovation, as well as environmental protection industries are more energy efficient than others. Sun and Anwar [33] explored the relationship between electricity consumption, industrial production, and entrepreneurship in Singapore's manufacturing sector.…”
Section: Conceptual Background With a Literature Reviewmentioning
confidence: 99%